Anti-Inflammatory Strategy for M2 Microglial Polarization Using Retinoic Acid-Loaded Nanoparticles - Marta Machado-Pereira; Tiago Santos; Lino Ferreira; Liliana Bernardino; Raquel Ferreira (Mediators of Inflammation)
Inflammatory mechanisms triggered by microglial cells are involved in the pathophysiology of several brain disorders, hindering repair. Herein, we propose the use of retinoic acid-loaded polymeric nanoparticles (RA-NP) as a means to modulate microglia response towards an anti-inflammatory and neuroprotective phenotype (M2). RA-NP were first confirmed to be internalized by N9 microglial cells; nanoparticles did not affect cell survival at concentrations below 100 μg/mL. Then, immunocytochemical studies were performed to assess the expression of pro- and anti-inflammatory mediators. Our results show that RA-NP inhibited LPS-induced release of nitric oxide and the expression of inducible nitric oxide synthase and promoted arginase-1 and interleukin-4 production. Additionally, RA-NP induced a ramified microglia morphology (indicative of M2 state), promoting tissue viability, particularly neuronal survival, and restored the expression of postsynaptic protein-95 in organotypic hippocampal slice cultures exposed to an inflammatory challenge. RA-NP also proved to be more efficient than the free equivalent RA concentration. Altogether, our data indicate that RA-NP may be envisioned as a promising therapeutic agent for brain inflammatory diseases.